1997
DOI: 10.1111/j.1432-1033.1997.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Interstitial Collagenase (Matrix Metalloproteinase‐1) Promoter Activity by Fibroblast Growth Factor

Abstract: Basic fibroblast growth factor (bFGF) is a pleiotropic factor that is implicated in tissue remodeling. The growth factor is capable of up-regulating the expression of the interstitial collagenase (matrix metalloproteinase-1 or MMP-1) gene. In this study, the full-length human MMP-1 promoter, spanning 4.3 kb, was sequenced and the regulatory control of its activity by bFGF was examined in NIH3T3 fibroblasts. Several regulatory sequences, including five activator protein-1 (AP-l), five activator protein-2 (AP-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Because etoposide induces both AP-1 and NFb (52), two positive regulators of hMMP-1 expression, it is not surprising to see hMMP-1 induction by etoposide in Saos-2 cells. Lack of hMMP-1 induction by etoposide in U2-OS cells, however, implies that etoposide-activated p53 executes a suppressive activity, thus diminishing the Ap-1/NFb effect (11,13,15,16).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Because etoposide induces both AP-1 and NFb (52), two positive regulators of hMMP-1 expression, it is not surprising to see hMMP-1 induction by etoposide in Saos-2 cells. Lack of hMMP-1 induction by etoposide in U2-OS cells, however, implies that etoposide-activated p53 executes a suppressive activity, thus diminishing the Ap-1/NFb effect (11,13,15,16).…”
Section: Figmentioning
confidence: 99%
“…Because etoposide induces both AP-1 and NFb (52), two positive regulators of hMMP-1 expression, it is not surprising to see hMMP-1 induction by etoposide in Saos-2 cells. Lack of hMMP-1 induction by etoposide in U2-OS cells, however, implies that etoposide-activated p53 executes a suppressive activity, thus diminishing the Ap-1/NFb effect (11,13,15,16).During the preparation of this manuscript, Aupperle et al (53) reported that the growth rate, invasiveness, and resistance to apoptosis induced by reactive oxygen species in rheumatoid and normal fibroblast-like synoviacyte increased significantly after endogenous p53 protein was inactivated with virus 18 E6 protein. However, no effect on collagenase mRNA accumulation was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AP1 mediates signaling of the FGF, but not activin, receptor during mesoderm induction, and AP1/Jun is a key signaling molecule in the development of posterior structure (45). FGF2 increases the transcription of matrix metalloproteinase 1 in NIH3T3 fibroblasts via AP1 (46), and induces binding of nuclear proteins from osteoblast-like ROS17/2.8 cells to consensus AP1 (10). These findings indicate that AP1 may be a crucial response element for FGF2-induced transcription.…”
Section: Discussionmentioning
confidence: 69%
“…The pcDNA3.1 vector containing a 2.2-kb fragment of the MMP-1 promoter (derived from pCLCAT3 (ref. 19))/luciferase construct (derived from pGL3) and pRL-SV40 plasmid were used for measuring MMP-1 promoter activity in this study.…”
Section: Materials and Methods Chemicals And Reagentsmentioning
confidence: 99%